Education expansion in hard times: An example from the Third World - London, Norrel A. (1991)
This article discusses the attempts of the Government of Trinidad and Tobago to provide for the education of a neglected and unfortunate group of students denied access to secondary education due to scarce financial resources. With no money to build and equip facilities, Trinidad and Tobago resorted to school clustering in order to further the education of post-primary students. The programme is analysed and evaluated with attention to its ideological, technical, social, and content perspectives
Keywords: Post primary students